KARAKTERISTIK MORFOLOGI DAN DISTRIBUSI KARBOHIDRAT NETRAL PADA UTERUS KELELAWAR BUAH (Pteropus vampyrus) ASAL PULAU TIMOR - Yulfia Selan; Filphin A. Amalo; Inggrid Trinidad Maha; Antin Y. N. Widi; Cynthia D. Gaina; Beatrix Barut (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Timorese fruit bat(Pteropusvampyrus)is the only fly mammalian with its unique behavior which hanging upside down inspite of its pregnancy. This research is aimed to reveal the morphology of the Timorese fruit bats and the distribution of neutral carbohydrate within this organ. Three uterus samples derived from three different Timorese fruit bats were used in the research.Both macroscopical and microscopical examinations using H&E and PAS methods were applied. Macroscopically, Timorese fruit bats showedsoft reddish white duplex uterus. Meanwhile microscopically, endometrium consisted of epithelial layer and lamina propria and was the place where simple tubular glands located. The epithelial layer comprised of simple cylindric secretory cells and ciliated cells. Neutral carbohydrate distribution was seen within this epithelial layer. Myometrium was a thick circular smooth muscle layer which consisted of smooth muscle separated by collagen and elastic fibre. Perimetrium was a visceral layer and consisted of mesothelial cells.